Variasi Genetik Attacus atlas L. (Lepidoptera: Saturniidae) Berdasar Penanda Molekuler ISSR (Inter Simple Sequence Repeat) - Puspa Pratiwi, Auronita (Biogenesis: Jurnal Ilmiah Biologi, 2014)
Attacus atlas is one of potent silk-producing insect and possesses a significant economic value. A. atlas is part of genus Attacus which inhabits in several quite large areas. A.atlas can be found in Sumatera, Java, Borneo, Halmahera Islands, and Papua. Mostly, species which inhabits in wide spread area, has a high level of diversity. Applied studies on Antheraea dan Samia cynthia ricini showed that geographical differences led to genetic variations occurred upon those species. The aim of this research was to study and analyze the genetic variation A. Atlas, which is obtained from multiple sampling locations, ie Berbah, Dlingo, Ngawen, and Pracimantoro, based on ISSR marker. Analysis of genetic variation performed with 4 ISSR primer, ISSR1, ISSR2, ISSR6, and ISSR7 gave forth high genetic variations among individuals of A.atlas by indicating the average polymorphic percentage of all primer of 97,78%. Clustering analysis with unweighted pair group with arithmetic average (UPGMA) method resulted dendrogram that exhibiting similarity values among individuals in range between 61% - 87% and clustered into two main clusters at 61% similarity value. The first cluster consists of samples taken from from Dlingo, Ngawen and Pracimantoro which has elevation above 200 m asl, while the second cluster consists of samples originating from Berbah which has elevation below 200 m asl. Amplification used 4 ISSR primer performed 2 monomorphic loci and 82 polymorphic loci. Monomorphic at 300 bp showed by ISSR2 and at 1800 bp showed by ISSR7 may be a candidate locus identifier species of A. atlas.Keywords: Attacus atlas, genetic variation, PCR-ISSR